CMOS mm-wave transceivers for Gbps wireless communication - 池保勇 宋政 况立雪 贾海昆 孟祥雨 王志华 (Journal of semiconductors, 2016)
The challenges in the design of CMOS millimeter-wave （mm-wave） transceiver for Gbps wireless com- munication are discussed. To support the Gbps data rate, the link bandwidth of the receiver/transmitter must be wide enough, which puts a lot of pressure on the mm-wave front-end as well as on the baseband circuit. This paper discusses the effects of the limited link bandwidth on the transceiver system performance and overviews the band- width expansion techniques for mm-wave amplifiers and IF programmable gain amplifier. Furthermore, dual-mode power amplifier （PA） and self-healing technique are introduced to improve the PA＇s average efficiency and to deal with the process, voltage, and temperature variation issue, respectively. Several fully-integrated CMOS mm-wave transceivers are also presented to give a short overview on the state-of-the-art mm-wave transceivers.